CALCULATION OF THREE-PHASE CIRCUIT WITH ARBITRARY NUMBER OF LOADS - Berzan V. (Problems of the Regional Energetics)
An algorithm for calculating the normal and emergency modes of three-phase circuits with distributed loads is elaborated. We propose to divide the required unknown currents into two groups: load currents are considered as principal, and currents in the other circuit branches are considered as complementary. This approach allows calculating at the first phase the load currents, and then other currents using the first Kirchhoff's law. The form of the matrix equation and rules of matrix coefficients composition for each phase depends on the number of loads connected to the phases of the circuit. Matrix equation includes 3n unknown currents. The proposed method allows calculating both the symmetric and asymmetric modes in the three-phase unbalanced network, using the same calculation algorithm. The fault modes, such as a single-phase, two-phase, three-phase and phase-to-phase short-circuits as well as the open circuits with some phase loads (simulation of the no-load mode in any node and in any phase of the circuit), could be also calculated.